Effect of cumulative exposure to corticosteroid and DMARD on radiographic progression in rheumatoid arthritis: results from the ESPOIR cohort. (22nd May 2018) - Louveau, Baptiste; De Rycke, Yann; Lafourcade, Alexandre; Saraux, Alain; Guillemin, Francis; Tubach, Florence; Fautrel, Bruno; Hajage, David
Abstract: Objectives: Several authors have tried to predict the risk of radiographic progression in RA according to baseline characteristics, considering exposure to treatment only as a binary variable (Treated: Yes/No). This study aims to model the risk of 5-year radiographic progression taking into account both baseline characteristics and the cumulative time-varying exposure to corticosteroids or DMARDs. Methods: The study population consisted of 403 patients of the Etude et Suivi des Polyarthrites Indifférenciées Récentes cohort meeting the 1987 ACR or 2010 ACR/EULAR criteria for RA at inclusion and having complete radiographic data at baseline and 5 years. Radiographic progression was defined at 5 years as a significant increase of the Sharp/van der Heidje score (smallest detectable difference ⩾5). The best logistic regression model was selected from the following: model including only clinico-biological baseline characteristics; model considering baseline characteristics and treatments as binary variables; and model considering baseline characteristics and treatments as weighted cumulative exposure variables. Results: Radiographic progression occurred in 143 (35.5%) patients. The best model combined anti-citrullinated peptide antibody positivity, ESR, swollen joint count >14 and erosion score at baseline, as well as corticosteroids, MTX/LEF (MTX or LEF) and biologic DMARDs (bDMARDs) as weighted cumulative exposure variables. Recent cumulative exposure to high doses of corticosteroids (⩽ 3months) was significantly associated with the risk of 5-year radiographic progression and a significant protective association was highlighted for a 36-month exposure to bDMARDs. Conclusion: Corticosteroids and bDMARDs play an important role in radiographic progression. Accounting for treatment class and intensity of exposure is a major concern in predictive models of radiographic progression in RA patients.